2014
DOI: 10.1038/ijo.2014.36
|View full text |Cite
|
Sign up to set email alerts
|

Alarmin high-mobility group B1 (HMGB1) is regulated in human adipocytes in insulin resistance and influences insulin secretion in β-cells

Abstract: These findings show, for the first time, that HMGB1 expression and release by human adipocytes is altered by inflammatory conditions as those imposed by obesity and insulin resistance. Our data reveal a novel role for HMGB1 as a stimulatory factor of insulin secretion of β-pancreatic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 48 publications
2
57
0
Order By: Relevance
“…This finding is not extremely surprising since HMGB1 and -2, as damage-associated molecular pattern molecules, are late mediators of noninfectious systemic inflammation. Recently, a study conducted in humans demonstrated that the intracellular distribution of HMGB1 is modified in a state of insulin resistance and that HMGB1 is a stimulatory factor of ␤-pancreatic cell insulin secretion, supporting a role for inflammation regulators in glucose homeostasis (17). Moreover, a strong association between HMGB1 and liver disease has been reported previously (7), even if the role of HMGB1 in the association between metabolic distress and liver disease is not fully understood.…”
Section: E752 Liver Protein Profiles In Diabetesmentioning
confidence: 97%
“…This finding is not extremely surprising since HMGB1 and -2, as damage-associated molecular pattern molecules, are late mediators of noninfectious systemic inflammation. Recently, a study conducted in humans demonstrated that the intracellular distribution of HMGB1 is modified in a state of insulin resistance and that HMGB1 is a stimulatory factor of ␤-pancreatic cell insulin secretion, supporting a role for inflammation regulators in glucose homeostasis (17). Moreover, a strong association between HMGB1 and liver disease has been reported previously (7), even if the role of HMGB1 in the association between metabolic distress and liver disease is not fully understood.…”
Section: E752 Liver Protein Profiles In Diabetesmentioning
confidence: 97%
“…Many studies have shown the positive correlation between circulating HMGB1 levels and BMI [8][9][10] and it has been also reported that the expression of HMGB1 in adipose tissue is altered in case of obesity. 3,8,11 This difference in HMGB1 expression has been attributed to inflammation insofar as it triggers HMGB1 secretion from cells derived from the stromal fraction of adipose tissue (ASCs), whereas mature adipocytes do not contribute to this secretion.…”
Section: Discussionmentioning
confidence: 99%
“…3,8,11 This difference in HMGB1 expression has been attributed to inflammation insofar as it triggers HMGB1 secretion from cells derived from the stromal fraction of adipose tissue (ASCs), whereas mature adipocytes do not contribute to this secretion. 3 Here we investigated the effects of exogenous disulfide HMGB1 on cultured primary human adipocytes and our results prove that HMGB1 may contribute to chronic and low grade inflammation by its effect on adipocytes, as it has been demonstrated in SW872 pre-adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating HMGB1 is positively associated with body mass index, while adipose HMGB1 mRNA levels correlate with the expression of inflammatory markers [24]. Insulin resistance modifies the intracellular distribution of HMGB1 in human adipocytes, with HMGB1 being predominantly nuclear in lean and obese normoglycemic individuals while localized to the cytosol in obese type 2 diabetic patients, and HMGB1 acts as a stimulatory factor of insulin secretion of β-cells [24]. HMGB1 is suggested to act as an adipokine contributing to low-grade inflammation in fat tissue [25].…”
Section: Discussionmentioning
confidence: 97%
“…Several reports indicate that HMGB1 is a pro-inflammatory cytokine which may contribute to the pathogenesis of micro-and macrovascular complications in diabetes [18][19][20][21][22][23]. Circulating HMGB1 is positively associated with body mass index, while adipose HMGB1 mRNA levels correlate with the expression of inflammatory markers [24]. Insulin resistance modifies the intracellular distribution of HMGB1 in human adipocytes, with HMGB1 being predominantly nuclear in lean and obese normoglycemic individuals while localized to the cytosol in obese type 2 diabetic patients, and HMGB1 acts as a stimulatory factor of insulin secretion of β-cells [24].…”
Section: Discussionmentioning
confidence: 97%